Encapsulated Bdellovibrio Powder as a Potential Bio-Disinfectant against Whiteleg Shrimp-Pathogenic Vibrios - Haipeng Cao (Microorganisms, 2019)
Liquid preparations of bdellovibrios are currently commercialized as water quality improvers to control bacterial pathogens in whiteleg shrimp Penaeus vannamei. However, the efficacy of these liquid preparations is significantly impaired due to a dramatic loss of viable cells during long-term room temperature storage. Thus, new formulations of bdellovibrios are greatly needed for high-stablility room-temperature storage. In the present study, the encapsulated powder of Bdellovibrio sp. strain F16 was prepared using spray drying with 20 g L−1 gelatin as the coating material under a spray flow of 750 L h−1, a feed rate of 12 mL min−1, and an air inlet temperature of 140 °C. It was found to have a cell density of 5.4 × 107 PFU g−1 and to have spherical microparticles with a wrinkled surface and a diameter of 3 μm to 12 μm. In addition, the encapsulated Bdellovibrio powder presented good storage stability with its cell density still remaining at 3.5 × 107 PFU g−1 after 120 days of room-temperature storage; it was safe for freshwater-farmed whiteleg shrimp with an LD50 over 1200 mg L−1, and it exhibited significant antibacterial and protective effects at 0.8 mg L−1 against shrimp-pathogenic vibrios. To our knowledge, this is the first report on a promising Bdellovibrio powder against shrimp vibrios with high stable room-temperature storage.